Increased arterial stiffness assessed by pulse wave velocity in Behçet's disease and its association with the lipid profile. (13th February 2012) - Caldas, C.A.M.; Borba, E.F.; Bortolotto, L.A.; Medeiros, D.M.; Bonfa, E.; Gonçalves, C.R.
Abstract Objective To evaluate the structural and functional properties of vessels in Behçet's Disease (BD) using carotid‐femoral pulse wave velocity (PWV) and an echo‐tracking system. Methods BD patients without traditional cardiovascular risk factors were selected. All BD patients performed PWV and carotid ultrasound. BD patients were divided into groups based on the presence of systemic (vascular and/or ocular and/or central nervous system involvement) and vascular involvement. Healthy controls age‐ and sex‐matched with the same exclusion criteria were selected. Results A total of 23 BD patients (mean age 35.0 ± 7.6 years) had significantly higher PWV levels compared with controls (8.48 ± 1.14 vs. 7.53 ± 1.40 m/s, P = 0.017). Intima‐media thickness (594.87 ± 138.61 vs. 561.08 ± 134.26 μm, P = 0.371), diastolic diameter (6383.78 ± 960.49 vs. 6447.65 ± 1159.73 μm, P = 0.840), distension (401.95 ± 117.72 vs. 337.91 ± 175.36 μm, P = 0.225) and relative distension (6.26 ± 2.83 vs. 5.42 ± 2.46 μm, P = 0.293) were similar in both groups. The systemic disease group had significantly higher levels of PWV (8.79 ± 1.21 vs. 7.88 ± 0.72 m/s, P = 0.036) compared to those with exclusive mucocutaneous manifestations. BD patients with vascular involvement had similar PWV and echo‐tracking parameters compared to those without vascular involvement (P > 0.05), but had higher total and LDL cholesterol levels (P = 0.019 and P = 0.012, respectively). The multivariate linear regression analysis identified triglycerides as the most important factor in increasing PWV levels (P = 0.001) in BD. Conclusions PWV is more useful than carotid ultrasound in detecting structural and functional vascular damage in BD and emphasizes the role of the disease itself in promoting these alterations. Our findings also reinforce the need for rigorous control of all risk factors in BD, particularly lipoproteins.